The Effect of Cannabidiol on Subjective Responses to Endurance Exercise: A Randomised Controlled Trial - Danielle McCartney; Christopher Irwin; Zeeta Bawa; Blake Palmer; Ayshe Sahinovic; Nathan Delang; Gregory R. Cox; Ben Desbrow; Namson S. Lau; Iain S. McGregor (SpringerOpen, 2024)
Abstract Background Exercise is known to improve health. However, it can be unpleasant, often inducing negative feelings, or 'affect'. Cannabidiol (CBD), a non-intoxicating constituent of the cannabis plant, has been reported to enhance the subjective experience of exercise; specifically, in trained individuals performing fixed-intensity endurance activity. Here, we investigated the effects of CBD on subjective responses to exercise under more ecologically valid conditions; namely, in recreationally active individuals performing self-paced endurance activity. Methods A randomised, double-blind, placebo-controlled, crossover trial was conducted at Griffith University between July 17 and August 28, 2023. Griffith University students studying sports nutrition were invited to take part, with eligible volunteers ≥ 18 years of age and able to perform endurance exercise. Participants ingested placebo or 150 mg CBD in two soft-gel capsules 90 min before completing a self-paced 25-lap (10 km) run around an outdoor athletics track (400 m, synthetic). The primary outcomes were affective valence during exercise, assessed on completion of laps 6, 12, 18 and 24 using the 'Feelings Scale', and positive and negative affect, assessed at baseline, pre-run and post-run using the 'Positive and Negative Affect Schedule'. Exercise enjoyment, motivation and self-efficacy, the core features of the 'runner's high' (i.e., euphoria, pain, anxiety, sedation), perceived exertion and run time were also assessed. Results Fifty-two participants were randomised and 51 were included in the final sample (n = 22 female; 22 [21-25] years). Exercise induced negative affect (i.e., at the time of undertaking) and increased pain. CBD did not counteract either response. In fact, CBD had no significant effects on any of the outcomes measured. In contrast, exercise, once completed, increased positive affect, and decreased negative affect and anxiety. Conclusions CBD (150 mg, oral) does not appear to enhance the subjective experience of self-paced endurance exercise in recreationally active individuals. Nor, however, does it appear to compromise it. These findings suggest that CBD use is safe under exercise conditions and unlikely to impede physical activity participation. Our study also reaffirms the powerful mood-enhancing effects of exercise. Trial Registration Registered with the Australian New Zealand Clinical Trials Registry ( www.anzctr.org.au ) on May 31, 2023 (Trial ID: ACTRN12623000593639).